NATURAL DESTRUCTION FROM HEAVY METAL PERSPECTIVE: ECOCRITICAL READING OF BURGERKILL’S SELECTED SONG LYRICS - Widiasmoro, Yohanes Mahatmo Suryo (Lire Journal (Journal of Linguistics and Literature), 2022)
This study aims to analyze two song lyrics titled “Hancur” and “Tinggalkan Aku Terdiam” from the Indonesian heavy metal band Burgerkill in order to see how environmental destruction in Indonesia is represented through heavy metal song lyrics. The ecological damage caused by natural exploitation has reached its critical point. The damage is almost beyond repair. Thus, this study tries to scrutinize how musicians represent their concerns on ecological damage. In doing this, this research uses the theory of ecocriticism as the foundational theory in order to scrutinize the texts. Then, this study uses a qualitative-interpretative method which is commonly applied in the study of literary texts. The results show that, firstly, “Hancur” song lyric describes the current state of nature in Indonesia. It shows the neglected environment after its resources are dredged by some people. Meanwhile, “Tinggalkan Aku Terdiam” represent the disappointment and anger of nature towards irresponsible people, it utilizes the first-person point of view to represent as if the nature who leave without any restoring effort after exploiting the nature. Hence, it can be said that, this analysis of the depiction of the ecological destruction is one of the efforts to expedite the pro-environmental movement for natural preservation.